2018
DOI: 10.1093/jxb/ery373
|View full text |Cite
|
Sign up to set email alerts
|

Combining high-throughput micro-CT-RGB phenotyping and genome-wide association study to dissect the genetic architecture of tiller growth in rice

Abstract: Combining high-throughput micro-CT-RGB phenotyping with genome-wide association study reveals the genetic architecture of tiller development in the indica subpopulation of rice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…To benefit more labs, it is important to decrease the unit cost associated with high-throughput phenotyping not only in the lab but also in the field (Hawkesford and Lorence, 2017). Another trend is to increase the number and quality of quantified traits, especially novel traits or those requiring labor-intensive and destructive measurement; i.e., tiller growth (Wu et al, 2019) or panicle development (Jhala and Thaker, 2015) by X-ray CT.…”
Section: Groundmentioning
confidence: 99%
See 2 more Smart Citations
“…To benefit more labs, it is important to decrease the unit cost associated with high-throughput phenotyping not only in the lab but also in the field (Hawkesford and Lorence, 2017). Another trend is to increase the number and quality of quantified traits, especially novel traits or those requiring labor-intensive and destructive measurement; i.e., tiller growth (Wu et al, 2019) or panicle development (Jhala and Thaker, 2015) by X-ray CT.…”
Section: Groundmentioning
confidence: 99%
“…Here, we focus on genetic studies that have directly benefited from mechanized phenotyping platforms (Table 2), both within the laboratory and in the field. The phenotypic data listed in Table 2 can be categorized into organ-/tissue-related traits (Leiboff et al, 2015;Wu et al, 2019), plant morphological and leaf architecture traits (Bac-Molenaar et al, 2015;Yang et al, 2015;Condorelli et al, 2018), root anatomical traits (Courtois et al, 2013;Shi et al, 2013;Xie et al, 2017), biomass-or growth-related traits (Busemeyer et al, 2013b;Muraya et al, 2017;Zhang et al, 2017), drought-and salinity responserelated traits (Honsdorf et al, 2014;Al-Tamimi et al, 2016;Guo et al, 2018a;Condorelli et al, 2018), and yield-related traits (Yang et al, 2014;Crowell et al, 2016;Zhou et al, 2019), which have been used in genetic mapping and are discussed in the following.…”
Section: High-throughput Phenotyping and Genetic Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we outline steps for the high-throughput µCT scanning of small (< 2 cm) fossils, meant to facilitate advanced exploration of museum collections and allow researchers with limited access to specialized facilities the opportunity to maximize their investments. In contrast to other high-throughput µCT methods that have focused on clinical evaluations 32,33 or automated phenotyping of laboratory strains (e.g., mice 34 , rice 35 , zebrafish 36 ), we concentrate on the practical arrangement of accessioned museum specimens so that each individual can be identified and labelled in the 3D volume, followed by long-term storage and archiving. We illustrate this method using vertebrate (reptile, amphibian and mammal) fossils from the paleontological collections of Queensland Museum, Australia, as part of a larger effort to identify changes in morphology and species assemblages over geological time.…”
Section: Introductionmentioning
confidence: 99%
“…Another GWAS led to the identification of a TN-associated 200 kb size locus that included 32 canidate genes (Lu et al, 2015c ). Dozens of loci associated with both TN variation (Wu et al 2018 ) and tiller angle-variation (Dong et al 2016 ) were recently identified using different natural rice populations. Because TN is a complex trait and the genetic basis of tillering is not completely understood, more research is needed to fully understand the genetic architecture of rice TN variations and identify more loci associated with tiller numbers (LATNs) in diverse germplasms.…”
Section: Introductionmentioning
confidence: 99%